Academic Information System Audit Using Cobit 5 Domain APO Framework - Muthmainnah, Muthmainnah; Yulisda, Desvina; Ilhadi, Veri (International Journal of Engineering, Science and Information Technology, 2022)
The use of Information Technology (IT) in higher education is said to be useful if its application is in accordance with the vision and mission of the organization. Academic information system audit is a method of assessing or assessing academic information systems to ensure that the governance and management functions of the information system are implemented properly. Unimal is a university that has implemented information technology in its operational processes. In achieving the organization's vision, the use of IT in the organization must always be monitored so that the services provided to users can be maximized, including by conducting an audit process to identify the level of IT maturity so that IT management can find solutions from processes that are considered less than optimal. This study aims to measure the level of capability of Unimal Academic Information Technology using COBIT 5 Domain APO (Align, Plan, and Organise) in the APO01, APO02, APO04 and APO11 processes. The focus of the research is also based on the need for priority processes in the Malikussaleh University environment and research related to the APO domain has not been carried out. The purpose of this study in general is to analyze Academic Information Technology using the COBIT 5 framework in the APO domain at the Malikussaleh University, as well as to provide solutions for improving academic information technology and IT implementation at the Malikussaleh University.